Comparative Cost Analysis of Endoscopic versus Microscopic Endonasal Transsphenoidal Surgery for Pituitary Adenomas - Eseonu, Chikezie Ikechukwu; ReFaey, Karim; Garcia, Oscar; Salvatori, Roberto; Quinones-Hinojosa, Alfredo (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective This study presents a comparative analysis of cost efficacy between the microscopic and endoscopic transsphenoidal approaches, evaluating neurological outcome, extent of resection (EOR), and inpatient hospital costs.Design This study was a retrospective chart review.Setting This study was conducted at a tertiary care center.Participants The study group consisted of 68 patients with transsphenoidal surgeries between January 2007 and January 2014.Main Outcome Measures Two-sample t-tests and Pearson's chi-square test evaluated inpatient costs, quality-adjusted life years (QALYs), volumetric EOR, and neurological outcomes.Results Total inpatient costs per patient was $22,853 in the microscopic group and less ($19,736) in the endoscopic group (p = 0.049). Operating room costs were $5,974 in the microscopic group and lower in the endoscopic group ($5,045; p = 0.038). Operative time was 203.6 minutes in the microscopic group and 166.3 minutes in the endoscopic group (p = 0.032). The QALY score, length of hospital stay, and postoperative outcomes were found to be similar between the two cohorts. Multivariate linear regression modeling suggested that length of stay (p < 0.001) and operative time (p = 0.008) were important factors that influenced total inpatient costs following transsphenoidal surgery.Conclusion This study shows that transsphenoidal surgery is more cost effective with the endoscopic approach than with the microscopic approach and depends on efficiency in the operating room as well as reduction in the length of hospitalization.
Keywords: adenoma; costs; endoscopic; microscopic; pituitary; transsphenoidal